Further delineation of spondyloepimetaphyseal dysplasia Faden‐Alkuraya type: A RSPRY1‐associated spondylo‐epi‐metaphyseal dysplasia with cono‐brachydactyly and craniosynostosis. Issue 9 (31st July 2018) - Simsek‐Kiper, Pelin O.; Taskiran, Ekim Z.; Kosukcu, Can; Urel‐Demir, Gizem; Akgun‐Dogan, Ozlem; Yilmaz, Guney; Utine, Gulen E.; Nishimura, Gen; Boduroglu, Koray; Alikasifoglu, Mehmet
Abstract : Our understanding of the molecular basis of the genetic disorders of the skeleton has steadily increased, as the application of high‐throughput sequencing technology has expanded. One of the newcomers is Spondyloepimetaphyseal dysplasia Faden‐Alkuraya type. In this study, we aimed to further delineate the clinical, radiographic, and molecular findings of this entity in five affected individuals from two unrelated families. All patients have short stature, extremity deformities, facial dysmorphism and intellectual disability. The skeletal hallmarks include (a) mild spondylar dysplasia, (b) epimetaphyseal dysplasia of the long bones associated with coxa vara and genu valgum, (c) brachymesophalangy with cone‐shaped epiphyses, and (d) craniosynostosis. Unlike the previously reported clinical findings, all patients except one are normocephalic, and all share the clinical findings including craniosynostosis, varying degrees of intellectual disability, facial dysmorphism, and skeletal findings including pes planus, prominent heels, and pectus deformity. Interestingly one of the patients presented with a cemento‐ossifying fibrous lesion of the maxilla. Whole exome sequencing revealed a novel homozygous [c.377delT] [p.Ile126fs*] frameshift mutation at exon 2 in one family, while Sanger sequencing revealed a novel homozygous splice site mutation [c.516+2T>A] at exon 4/intron 4 border of RSPRY1 in the other family. In conclusion; we provide further evidence that Spondyloepimetaphyseal dysplasia Faden‐Alkuraya type is a RSPRY1‐associated skeletal dysplasia with a distinctive phenotype composed of spondyloepimetaphyseal dysplasia, cono‐brachydactyly, and craniosynostosis along with recognizable facial features and intellectual disability.